LGG-16. PREDICTORS OF OUTCOME IN BRAF-V600E PEDIATRIC GLIOMAS TREATED WITH BRAF INHIBITORS: A REPORT FROM THE PLGG TASKFORCE. (23rd April 2019) - Nobre, Liana; Zapotocky, Michal; Ryall, Scott; Stucklin, Ana Guerreiro; Bennett, Julie; Baroni, Lorena; Sumerauer, David; Zamecnik, Josef; Krskova, Lenka; Misove, Adela; Pavelka, Zdenek; Sterba, Jaroslav; et al.
Abstract: The BRAF-V600E mutation is found in 15–20% of pediatric low grade gliomas (PLGG) and result in worse outcome and higher risk of transformation to high grade gliomas (PHGG). Although ongoing trials are assessing the role of BRAF inhibitors (BRAFi) in these children, data are still limited. We aimed to report overall response rates and predictors of outcome in childhood BRAF-V600E gliomas. We collected clinical, imaging and molecular information of patients treated with BRAFi outside trials from centers participating in the PLGG taskforce. Response was calculated by RANO criteria and follow up data were collected for all patients. Sixty-six patients were treated with BRAFi (55 PLGG and 11 PHGG); median follow-up time was 1.5 years (0.1-5y). In PLGG, objective response (tumor reduction of >25%) was observed in 77% compared to 15% in a cohort treated with conventional chemotherapy (p CDKN2A deletion was not associated with lack of response, while specific enhancing patterns correlated strongly with response to BRAFi. Two-year PFS for the BRAF-V600E PLGG was 74% vs 47% for BRAFi vs chemotherapy, respectively (p=0.02). Our data reveal rapid, dramatic and sustained response of BRAF-V600E PLGG to BRAFi. These are in contrast to BRAF-V600E PHGG and non-enhancing PLGG. Additional molecular analyses are being performed to identify poor responders and emerging mechanisms of resistance in these tumors.